Tales from the Panchatantra - Chandrakant, Kamala; Edited by Anant Pai (Mumbai; Amar Chitra Katha, 2023)
Collection of the following titles: Crows and Owls, The Dullard and Other Stories, The Greedy Mother-in-Law
Keywords: Panchatantra tales; Animals talk